2011
DOI: 10.1128/ec.00006-11
|View full text |Cite
|
Sign up to set email alerts
|

Ccr4 Promotes Resolution of the Endoplasmic Reticulum Stress Response during Host Temperature Adaptation in Cryptococcus neoformans

Abstract: Adaptation to host temperature is a prerequisite for any pathogen capable of causing deep infection in humans. Our previous studies demonstrated that a Cryptococcus neoformans ccr4⌬ mutant lacking the major deadenylase involved in regulated mRNA decay was defective in host temperature adaptation and therefore virulence. In this study, the ccr4⌬ mutant was found to exhibit characteristics of chronic unfolded-protein response (UPR) engagement in both the gene expression profile and phenotype. We demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 31 publications
4
60
0
Order By: Relevance
“…The loss of UPR induction through deletion of the stress response mediators IRE1 and HXL1 impairs virulence and temperature adaptation (2). Likewise, prolonged ER stress resulting from the loss of mRNA degradation in a ccr4⌬ mutant also impairs temperature adaptation (1). Together, this information suggests that a balance of UPR induction and resolution is critical for successful temperature adaptation in C. neoformans.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The loss of UPR induction through deletion of the stress response mediators IRE1 and HXL1 impairs virulence and temperature adaptation (2). Likewise, prolonged ER stress resulting from the loss of mRNA degradation in a ccr4⌬ mutant also impairs temperature adaptation (1). Together, this information suggests that a balance of UPR induction and resolution is critical for successful temperature adaptation in C. neoformans.…”
mentioning
confidence: 80%
“…The mammalian host temperature exerts endoplasmic reticulum (ER) stress on C. neoformans, leading to a transient induction of the unfolded protein response (UPR) during temperature adaptation (1). The loss of UPR induction through deletion of the stress response mediators IRE1 and HXL1 impairs virulence and temperature adaptation (2).…”
mentioning
confidence: 99%
“…Decay of ER stress-responsive transcripts, including KAR2, OST2 (a subunit of the ER oligosaccharyltransferase complex), and ALG7 (lipid-linked Noligosaccharyltransferase), is delayed in cells lacking Ccr4 (which encodes mRNA deadenylase and is involved in mRNA stability) during ER stress response and host temperature adaptation (132). Furthermore, Rpb4, which encodes a RNA polymerase II subunit, controls the destabilization of KAR2 during temperature upshift (131).…”
Section: The Unfolded Protein Response (Upr) Signaling Pathwaymentioning
confidence: 99%
“…Recently, Havel et al 55 demonstrated that ER stress-responsive transcripts are regulated at the post-transcriptional level during adaptation of C. neoformans to host physiological temperature. During ER stress response and host temperature adaptation, the decay rates of ER stress-responsive transcripts, including KAR2, OST2 (a subunit of the ER oligosaccharyltransferase complex), and ALG7 (a lipid-linked N-oligosaccharyltransferase), are lower in cells null for the mRNA deadenylase-encoding CCR4 gene.…”
mentioning
confidence: 99%
“…During ER stress response and host temperature adaptation, the decay rates of ER stress-responsive transcripts, including KAR2, OST2 (a subunit of the ER oligosaccharyltransferase complex), and ALG7 (a lipid-linked N-oligosaccharyltransferase), are lower in cells null for the mRNA deadenylase-encoding CCR4 gene. 55 Furthermore, RBP4, which encodes an RNA polymerase II subunit, was shown to be involved in destabilizing the KAR2 transcript during temperature upshift. 56 Therefore, the mRNA degradation machinery regulated by Ccr4 and Rpb4 appears to provide an additional level of control to the UPR pathway, contributing to the cellular response to ER stress.…”
mentioning
confidence: 99%